The Impact of Transformational Leadership on School Culture - john Michael Sasan; Gemma R. Escultor; Vahid Norouzi Larsari (Ridwan Institute, 2023)
This qualitative study explores how transformational leadership affects school culture in high schools. The study interviewed five school heads, five teachers, and five students to examine the influence of transformational leadership practices on school culture. The findings indicate that transformational leadership practices, such as setting high expectations, building a sense of community, and focusing on student learning, can result in a positive school culture characterized by high levels of engagement and collaboration among staff and students. The study emphasizes the essential role of school leaders in shaping school culture. By implementing transformational leadership practices, school leaders can create a culture that empowers their staff and students, and fosters collaboration. However, the study also recognizes the challenges and limitations of transformational leadership; the need for school leaders to be aware of these challenges and works to address them. The study provides recommendations for school leaders and policymakers to effectively implement transformational leadership practices, including investing in professional development, fostering a culture of empowerment and support, and encouraging collaboration and teamwork. This study offers valuable insights into the impact of transformational leadership on school culture, highlighting the significance of creating a positive school culture that promotes student success and overall school excellence.